Epigenetic gene expression links heart failure to memory impairment. Issue 3 (20th January 2021) - Islam, Md Rezaul; Lbik, Dawid; Sakib, M Sadman; Maximilian Hofmann, Raoul; Berulava, Tea; Jiménez Mausbach, Martí; Cha, Julia; Goldberg, Maria; Vakhtang, Elerdashvili; Schiffmann, Christian; Zieseniss, Anke; Katschinski, Dörthe Magdalena; et al.
Abstract: In current clinical practice, care of diseased patients is often restricted to separated disciplines. However, such an organ‐centered approach is not always suitable. For example, cognitive dysfunction is a severe burden in heart failure patients. Moreover, these patients have an increased risk for age‐associated dementias. The underlying molecular mechanisms are presently unknown, and thus, corresponding therapeutic strategies to improve cognition in heart failure patients are missing. Using mice as model organisms, we show that heart failure leads to specific changes in hippocampal gene expression, a brain region intimately linked to cognition. These changes reflect increased cellular stress pathways which eventually lead to loss of neuronal euchromatin and reduced expression of a hippocampal gene cluster essential for cognition. Consequently, mice suffering from heart failure exhibit impaired memory function. These pathological changes are ameliorated via the administration of a drug that promotes neuronal euchromatin formation. Our study provides first insight to the molecular processes by which heart failure contributes to neuronal dysfunction and point to novel therapeutic avenues to treat cognitive defects in heart failure patients. Synopsis: Patients suffering from heart failure have an increased risk to develop age‐associated dementia. This study elucidates the underlying mechanisms and provides evidence that heart‐failure induced cognitive decline is linked to epigenetic changes that affect neuronal gene expression. Heart failure leads to hippocampal gene expression changes in mice. Heart failure induced aberrant neuronal gene expression was linked to hypoxia and ER stress pathways. Loss of H3K4me3 was identified as a key epigenetic change in heart failure induced cognitive impairment. Targeting H3K4me3 was able to reinstate memory function and transcriptome homeostasis in a mouse model for heart failure. Abstract : Patients suffering from heart failure have an increased risk to develop age‐associated dementia. This study elucidates the underlying mechanisms and provides evidence that heart‐failure induced cognitive decline is linked to epigenetic changes that affect neuronal gene expression.